THE EFFECT OF GAME-BASED LEARNING MODEL ASSISTED BY BAMBOOZLE ON THE MULTIPLICATION SKILLS OF ELEMENTARY SCHOOL STUDENTS - Irma Retno Rahayu; Diki Rukmana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Students’ skills in performing multiplication operations are low. The purpose of the study in this article is to determine the effect of the game-based learning model assisted by "Bamboozle" on the multiplication skills of the second-grade students at Islamic Elementary School in Al Hidayah in the academic year of 2021/2002. This study used experimental quantitative research with a One Group Pretest Posttest design. This study used a saturated sample as the sampling technique and tests as the data collection method. The results showed that the pre-treatment mean score of 63.33 was lower than the post-treatment mean score of 91.90. By using the Wilcoxon test data analysis method, the values of 21 samples increased from pre-test to post-test with an average increase of 11.00. In addition, by analyzing the Asymp value. Sig. (2-tailed) 0.000 < 0.05, it could be concluded that there was a significant effect of the game-based learning model assisted by the application of "Bamboozle" on the multiplication operation skills of the second-grade students at SD Islam Al-Hidayah in the academic year 2021/2022.